Relationship between Amount of Drugs Taken and Warfarin Adherence - Artha Woro Utami (Universitas PGRI Madiun, 2020)
Warfarin is a narrow therapeutic drug that needs to be monitored its use. Warfarin adherence is expected to improve warfarin control. However, the amount of drug taken can cause complications in its use which in turn can impact warfarin adherence. Therefore, this study aims to determine the relationship between the amount of medication taken with warfarin adherence. This study is an analytical observational study with a cross sectional design. The subjects of this study were adult patients (> 18 years old) at the cardiac clinic of PKU Muhammadiyah Yogyakarta Hospital who received warfarin and were willing to be a prescription. The number of research samples obtained was 35 patients. Measurement of adherence using a questionnaire Medication Adherence Rating Scale (MARS). Chi Square analysis was used to determine the relationship between the amount of medication taken and adherence to drinking warfarin. The results showed that there were 19 patients (54.3%) who took 4 drugs (54.3%) and 16 patients (45.7%) who took> 4 drugs. Patient adherence was divided into low and high adherence. A total of 18 patients (51.4%) had high adherence and 17 patients (48.6%) had low adherence. Based on the chi square analysis, there is a relationship between the number of drugs taken and adherence to taking warfarin (p = 0.04 <0.05).